The diagnostic advantage of immature platelet fraction and platelet indices in thrombocytopenia cases: Tertiary care center study - Rachana Pachkawade; Girija; Yaranal PJ; Pratima Manohar Pattar (Asian Journal of Medical Sciences)
Background: Thrombocytopenia, characterized by low platelet counts, is a common hematological disorder with diverse causes, complicating diagnosis. Distinguishing between central and peripheral causes is crucial for appropriate management. Automated hematology analyzers measuring platelet indices, especially immature platelet fraction (IPF), provide valuable insights, aiding early diagnosis, preventing unnecessary transfusions, and improving patient care.